2016
DOI: 10.1021/acs.molpharmaceut.6b00696
|View full text |Cite
|
Sign up to set email alerts
|

PEGylation of Reduced Graphene Oxide Induces Toxicity in Cells of the Blood–Brain Barrier: Anin Vitroandin VivoStudy

Abstract: Polyethylene glycol (PEG) coating has been frequently used to improve the pharmacokinetic behavior of nanoparticles. Studies that contribute to better unravel the effects of PEGylation on the toxicity of nanoparticle formulation are therefore highly relevant. In the present study, reduced graphene oxide (rGO) was functionalized with PEG, and its effects on key components of the blood-brain barrier, such as astrocytes and endothelial cells, were analyzed in culture and in an in vivo rat model. The in vitro stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
67
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(73 citation statements)
references
References 40 publications
3
67
0
Order By: Relevance
“…12 These nanomaterials may exert differing degrees of toxicity in animals or cell models depending on the administration route or penetration through physiological barriers such as the BBB. 11,13,14 However, toxicological information on GO materials remains limited. In this study, we examined the neurotoxic effects of graphene family nanomaterials using the PC12 cell model.…”
Section: Discussionmentioning
confidence: 99%
“…12 These nanomaterials may exert differing degrees of toxicity in animals or cell models depending on the administration route or penetration through physiological barriers such as the BBB. 11,13,14 However, toxicological information on GO materials remains limited. In this study, we examined the neurotoxic effects of graphene family nanomaterials using the PC12 cell model.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced GO conjugated with PEG but not unconjugated GO induced a significant decrease in viability at 100 μg/mL in primary isolated rBMVECs. This decrease in viability was related to a decrease in the expression of claudin‐5 and OC (Mendonca et al, ). In the present study, we also observed an increase in BBB permeability and decrease in viability at 50 and 100 μg/mL as well as a decrease in the expression of OC at the highest concentration tested, suggesting that even when the type of graphene used in all three studies was different, all of them still induced deleterious effects to the BBB.…”
Section: Discussionmentioning
confidence: 99%
“…Administration of reduced GO conjugated with polyethylene glycol (PEG) also induced a decrease in the expression in OC in vivo. In addition, reduced GO conjugated with PEG, but not reduced GO alone decreased the viability of rat (r)BMVECs in culture, and decreased the expression of claudin-5 and OC (Mendonca et al, 2016), suggesting that reduced GO induced a disruption of the BBB.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…Few‐layer graphene‐induced DNA damage in primary human umbilical vein endothelial cells . Reduced graphene oxide have been shown to have significant degree of toxicity on rat brain endothelial cells although the toxicity could be dampened with PEGylation . Graphite, multiwalled carbon nanotubes, and fullerenes inhibit vascular endothelial growth factor—and fibroblast growth factor–induced angiogenesis may further aggravate the potent effects of exposing the endothelium to these nanomaterials .…”
Section: Nanocarbons and The Endotheliummentioning
confidence: 99%